A compact microstrip-fed open slot antenna for dual slant polarization with good isolation. Issue 11 (23rd July 2016) - Krishna, R. V. S. Ram; Kumar, Raj
Abstract: A V-shape slot antenna for dual slant polarization is proposed. The slot is the union of two stepped rectangular slots tilted at ±45° with the vertical. Each section of the slot is excited using a microstrip feed line printed on the other side of the substrate. The feed is also stepped and bent so as to cross the slot at right angles. The decoupling between the ports is provided by means of narrow rectangular stubs placed at the intersection of the slot arms. Measurements taken on the fabricated prototype indicate an impedance bandwidth from 3.3 to 12 GHz with isolation better than 15 dB across the band. The aperture electric field distributions as well as far field radiation patterns are used to verify the dual slant polarization achieved with the antenna. The time domain characterization of the antenna is done by calculating the fidelity factor which is found to be >0.75 indicating suitability of the antenna for pulse transmission. For determining the diversity behavior, the envelope correlation coefficient is calculated and found to be below 0.004. The antenna has a peak gain from 4 to 6 dBi. A modified design of the antenna is also presented with impedance bandwidth from 3 to 12 GHz and isolation better than 20 dB from 3.7 GHz onwards. With compact features and wideband return loss and isolation, the antennas are expected to be useful for diversity applications in ultra wideband communication devices such as MIMO wifi, imaging radars, and polarimetric sensing devices.